A study on design and implementation of dynamic location tracking system for locating remote control - Hyun Seo, Sung; Hyun Ro, Kwang (International Journal of Engineering and Technology, 2018)
With the development of IoT technology, there is a growing demand for location based services for checking the mobility and identity of users, and remote controls for remote control of household appliances or electronic devices are used for home appliances or electronic devices there are many functions that are not available.In this case, when the remote controller is lost, there are difficulties in that a large number of home appliances or electronic devices can only be started by a limited operation or can’t operate various operations.Especially, many people are losing a lot of remote control in everyday life, and the problem of wasting a considerable amount of time in finding a remote control is also happening.In order to solve this problem, the present invention proposes a method of opening a remote control search application content, registering a unique product number assigned to the remote control, generating a location notification request signal for requesting the location information of the remote controller, And then displays the captured location or dynamic model detected from the location notification response signal on the basis of the indoor framing for 2D or the indoor framing for 3D, It will be able to quickly and accurately locate the remote control that emits the beacon signal. In other words, in this paper, the application contents for remote controller search are opened to register a unique product number assigned to the remote controller, a location notification request signal for requesting the location information of the remote controller, and a location notification response And then displays the captured spot or dynamic model detected from the signal on the beacon for 2D or the 3D model for 3D.In the future, the research method to be carried out is limited to grasp the object information only by the remote controller (one single article object), but it is difficult to quickly recognize the object information transmitted from various objects having mobility used in the home or work We plan to implement and design an algorithm that optimizes the received signal strength of the BLE beacon so that there is no loss of beacon signal in a room that is subject to better system and multipath effects.
Keywords: Remote Control; Communication Terminal; Position Tracking; Beacon Signal; Position Notification Request Signal; Position Notification Response Signal.